2018
DOI: 10.3892/mmr.2018.9405
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA lnc‑GNAT1‑1 inhibits gastric cancer cell proliferation and invasion through the Wnt/β‑catenin pathway in Helicobacter�pylori infection

Abstract: The aim of the present study was to investigate the effect of long non‑coding (lnc)‑G protein subunit α transducin 1 (GNAT1)‑1 in gastric cancer cells infected with Helicobacter (H.) pylori. Reverse transcription‑quantitative polymerase chain reaction was used to assess lnc‑GNAT1‑1 expression in normal gastric and gastric cancer cells infected with H. pylori. The overexpression of lnc‑GNAT1‑1 in SGC‑7901 and MNK45 cells was induced by transfection. Migration and invasion assays were performed in transfected ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“… 7 Studies have recognized that lncRNA, as a multitalented transcriptional and posttranscriptional regulator of key cancer pathways, possesses lots of biological functions involved in many types of cancer progression, 8 such as hepatocellular carcinoma, 9 lung cancer (LC), 10 colorectal cancer (CRC), 11 and gastric cancer. 12 A number of cross-sectional studies have suggested numerous lncRNAs being related to the development of ESCC. It has been reported that NORAD was correlated with tumor size and overall survival in ESCC.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Studies have recognized that lncRNA, as a multitalented transcriptional and posttranscriptional regulator of key cancer pathways, possesses lots of biological functions involved in many types of cancer progression, 8 such as hepatocellular carcinoma, 9 lung cancer (LC), 10 colorectal cancer (CRC), 11 and gastric cancer. 12 A number of cross-sectional studies have suggested numerous lncRNAs being related to the development of ESCC. It has been reported that NORAD was correlated with tumor size and overall survival in ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism is thought to be related to the regulation of the RKIP-NF-κB-Snail circuit (Ye et al, 2016). Downregulation of lnc-GNAT1-1 was observed in patients with gastric cancer and lower levels of Helicobacter pylori infection and increased expression levels of lnc-GNAT1-1 suppressed gastric cancer growth by inactivating the Wnt/β-catenin pathway (Liu et al, 2018). Against this background, we explored the roles of lnc-GNAT1-1 in liver cancer development and the mechanisms used by lnc-GNAT1-1 to exert modulatory effects on liver cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that lnc-GNAT1-1 plays an anti-tumor role in malignancies of the digestive tract, including colorectal (Ye et al, 2016) and gastric cancers (Liu et al, 2018). Nevertheless, there are no studies of lnc-GNAT1-1 in liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, growing evidence implies that altered expression of lncRNAs could be closely related to genesis and progression of numerous diseases, especially in cancers and viral infections ( Liu and Ding, 2017 ; Sun et al, 2020 ). Recently, numerous studies have provided evidence for the involvement of lncRNAs in bacterial infections, including Mycobacterium tuberculosis , Helicobacter pylori , Listeria monocytogenes , and so forth ( Liu et al, 2018 ; Li M. et al, 2019 ; Xu et al, 2019 ). However, few studies have evaluated the alternation of lncRNAs in obligate intracellular bacterium C. trachomatis .…”
Section: Introductionmentioning
confidence: 99%